Review ON ARTICLE BY LEGENINA T.B. "FORMATION OF POLITICAL IDENTITY" - G. V. Kosov (Современная наука и инновации, 2022)
The article discusses political identity as a process of correlation of the individual with a certain political organizations, party etc. The goals and objectives set out in the article, fully implemented in this study.